-9m+5=-6

Simple and best practice solution for -9m+5=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9m+5=-6 equation:


Simplifying
-9m + 5 = -6

Reorder the terms:
5 + -9m = -6

Solving
5 + -9m = -6

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -9m = -6 + -5

Combine like terms: 5 + -5 = 0
0 + -9m = -6 + -5
-9m = -6 + -5

Combine like terms: -6 + -5 = -11
-9m = -11

Divide each side by '-9'.
m = 1.222222222

Simplifying
m = 1.222222222

See similar equations:

| 2x+y-5=a | | 0.6=0.15x | | 5(t+1)=0 | | -2(d+6)=-18 | | 2x-39=61 | | 9x+2=12x-4 | | (5+6i)-(7-8i)= | | -1x-3=-2 | | 16/p=-4 | | 3x/2+6x+45=180 | | -3+7=8+2x | | 4(v+4)-6v=-2 | | 2r-36-15r=-50+r | | 4(v+1)-6=10 | | -8r=40 | | 14x+2y=40 | | Log(10)=1 | | 4x+3x-5x=-2 | | 3+3+5m-6+5m-6= | | 2(r-8)=10 | | 3(x+2)=-4 | | 4=19-c | | 6.4(x-4.5)=-25.6 | | -5(6y-7)-y=-4(y-2) | | ax+by=z | | 15q-9q+3=15 | | 1.6=2/5(7-3) | | 1.6=2/5(b-3) | | 2x+6+3x=31 | | 8ln(3x)=11 | | 15y-11y-20y+9=9 | | 2(1+3n)=2n |

Equations solver categories